Non-invasive diagnosis of pseudoaneurysm of left ventricle. - van Mechelen, R (1978)
A patient free of symptoms, with a pseudoaneurysm of the left ventricle after inferoposterolateral myocardial infarction, is reported. The diagnosis was established by nuclear cardiography and echocardiography of the left ventricle.